FAKTOR – FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PEMERINTAH DAERAH DI KABUPATEN/KOTA JAWA TENGAH (Studi Kasus pada Kabupaten dan Kota di Provinsi Jawa Tengah Tahun 2014 - 2016) - Rizky Zulfa Rihhadatul Aisy, 14.05.52.0272; Maryono, Maryono (Students' Journal of Accounting and Banking, 2018)
This study aims to examine the influence of leverage, legislative measures, intergovernmentl revenue, shopping area, and regional tax revenue on the district’s financial performance in Central Java. The population of this study is all 35 districts/cities in Central Java from the period 2014 to 2016 with 105 as total number of observations. The data used in this researches is secondary data, the analysis method used in this study is the Multiple Linier Regression Analysis. The study found that leverage, legislative measures, intergovernmental revenue and shopping area had no influence on regional financial performance. While regional tax revenue have significant and positive effect on regional financial performance. Keywords: Leverage, Legislative Measures, Intergovernmental Revenue, Shopping Area, Regional Tax Revenue, Regional Financial Performance